Região metropolitana de Feira de Santana: uma proposta de gestão - Santos Junior, Antonio Carlos Borges (2019)
This dissertation was based on some crucial assumptions: (i) the singular unity of the municipality is not enough to meet all the growing demands and needs of public services for the population, especially intermunicipal ones; (ii) members of MAFS municipalities are not able to attend all services in the scope, level, quality and quantity, so some service demands need to be shared jointly with other cities; (iii) many works need to be performed by connecting municipalities, since one alone does not have all the resources or revenue to make investments, or has no power to get them in the required amounts in higher instances; and (iv) although all cities appear to have the same needs, they do not have the same potentialities, features, spaces, adequate access. In its conception, the MAFS foresaw all the application and control of public policies, the interaction between the powers of the municipalities involved and the community’s manifestations. The management must be through sharing – as a classic model for organizing and solving problems and demands – within the administrative boundaries of municipalities. Therefore, it is proposed in the scope of this dissertation, a management model that seeks essential means to strengthen the economic and productive base of the region, integrating it through various organizational links. In this perspective, it was been suggested the creation of a Metropolitan Development Agency, with governance and shared decision-making, that will take care of the integration, the search for balance and the economic development. The scenarios to be studied by the Agency, that designs the regional future, will necessarily be supported on demands, benefits, priorities, availability of resources, shared participation with companies in the region, as well as the provision of resources and the creation of three investment funds which intends to attract national and foreign resources. The proposal also contemplates the formation of a Social Welfare Regime, and calls for a genuine participation of the many social forces, desires and needs, including the powers, in all spheres, as well as the institutions publics and privates to make the management of the MAFS worth